2007
DOI: 10.1002/pola.22031
|View full text |Cite
|
Sign up to set email alerts
|

Fast degradable poly(L‐lactide‐co‐ε‐caprolactone) microspheres for tissue engineering: Synthesis, characterization, and degradation behavior

Abstract: Polymeric scaffolds play a crucial role in engineering process of new tissues and effect the cell growth and viability. PLCL copolymers are found to be very useful during cell growth due to their elastic behavior and mechanical strength. Thus, low molecular weight PLCL copolymers of various ratios viz. PLCL(90/10), PLCL(75/25), PLCL(50/50) and PCL were synthesized by ring opening polymerization using stannous octoate as a catalyst. Synthesized polymers were characterized by GPC, 1 H-NMR, FTIR and XRD. The ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 34 publications
5
55
0
3
Order By: Relevance
“…This is catalysed by acidic conditions [17]. We chose this pH because it mimics the pH in the lumen of the native urethra and therefore it can be assumed that the degradation rate of these membranes most probably is similar to that in the urinary tract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is catalysed by acidic conditions [17]. We chose this pH because it mimics the pH in the lumen of the native urethra and therefore it can be assumed that the degradation rate of these membranes most probably is similar to that in the urinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…Although PCL is highly elastic and strain is more than 700 per cent at breakage [10], the degradation rate of PCL is rather slow for urothelial tissue engineering, taking up to 2 years [10,12]. Various poly-L-lactide-co-1-caprolactone (PLCL) compositions have been studied in tissue engineering applications [13][14][15][16][17][18], but the main focus has been on producing electrospun nanofibrous membranes. In our recent study [19], we showed that compression-moulded smooth PLCL membranes supported the proliferation and differentiation of hUCs better than human amniotic membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the hydrolytic degradation behavior of poly(D,L-lactide-co-ε-caprolactone) (PDLCL) and PLCL copolymers, the situation is much more complex than in PDLGA or PLGA copolymers, and contradictory results can be found in the literature [40][41][42]. In the case of PDLGA or PLGA copolymers, the addition of glycolide (below the limit where glycolide can also form crystalline domains) accelerates the degradation behavior of PLAs due to the incorporation of hydrolytically less resistant units and a reduction in the crystallinity of PLLA polymers.…”
Section: Polylactide and Its Copolyesters: Towards Tunable Mechanicalmentioning
confidence: 99%
“…In PLCL copolymers, the incorporation of ε-caprolactone (below the limit where ε-caprolactone can also form crystalline domains) to PLAs lowers the crystallization capability of PLLA, but will, at the same time, provide more hydrolytically resistant units. Although these two effects are antagonistic, the results found in literature indicate that the reduction in crystallinity affects the degradation behavior to a larger extent [40,41,43]. For example, Garkhal et al [40] compared the degradation behavior of three PLCLs having 90:10 (90% L-lactide, 10% ε-caprolactone), 75:25 and 50:50 compositions.…”
Section: Polylactide and Its Copolyesters: Towards Tunable Mechanicalmentioning
confidence: 99%
See 1 more Smart Citation